Toksisitas Ekstrak Metanol Spirulina sp terhadap nauplii Artemia sp. - Suryono Suryono; Ervia Yudiati (Universitas Diponegoro, 2011)
Abstract BSLT (Brine Shrimp Lethality Test) was conducted on crude ectract of Spirulina sp. The extraction was done by added methanol solution. The Spirulina extract tested to newly hatched Artemia sp. nauplii. The objective of this study was to analize the mortality of the nauplii dan to determine the LC50-24h level. The result showed that the bioactive compound of Spirulina sp had a high toxicity level (LC50-24h: 113.2 ppm). It can be concluded that this specific microalgae had a potential source of medicine. Keywords: Spirulina sp, BSLT,crude extract.